(3GdchcH GdKGbH aj CNHGQ GdTYQGA hZjQge ef Phi GdefGbHs - (3GHf YHO GdQMef , YHO GdbGOQ Hf YHO GdQMef GdCfOdSj,J (B1180 (3g` s
(3ChdgG (B:s
(3fMeOc jGef CfWb dSGf GdEfSGf s
(3BNQgG (B:s
(3hbO Je GdcJGH GdeHGQc HJeGe GdNGJeI s
(3GfXQ Qbe (B420 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B39s
Keywords: (3GdJGQjNs